2011
DOI: 10.1309/ajcpix52mbokticp
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating the “Atypia of Undetermined Significance/Follicular Lesion of Undetermined Significance” Category From the Bethesda System for Reporting Thyroid Cytopathology

Abstract: The "Atypia of Undetermined Significance/Follicular Lesion of Undetermined Significance (AUS/FLUS)" category in the Bethesda System for Reporting Thyroid Cytology is heterogeneous and includes both specimens with borderline cellularity/compromised quality and those with genuine atypia. We have used a reporting scheme that is similar to the Bethesda System but does not include an AUS/FLUS category. We retrospectively reviewed all reports on thyroid FNA and thyroidectomy specimens submitted to the Beth Israel De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 18 publications
6
72
2
1
Order By: Relevance
“…For example, in two of the studies cited in determining risks of malignancy for the Bethesda diagnostic categories, the data were from1980-1997 and 1995-2004 (23,24). In the study by Jung et al (27)(28)(29). Similarly, our rate of malignancy for the SUS category is also comparable to these groups (28,29).…”
Section: Strickland Et Alsupporting
confidence: 81%
“…For example, in two of the studies cited in determining risks of malignancy for the Bethesda diagnostic categories, the data were from1980-1997 and 1995-2004 (23,24). In the study by Jung et al (27)(28)(29). Similarly, our rate of malignancy for the SUS category is also comparable to these groups (28,29).…”
Section: Strickland Et Alsupporting
confidence: 81%
“…29,30 In our pediatric population, the overall rate of thyroid malignancy was 35%, and the vast majority of these malignancies were PTC (95%). This rate of malignancy is comparable to the range of malignancy (20%-50%) reported by other studies examining surgically resected pediatric and adult thyroid nodules, 2,5,22,30,31 and likely overestimates the true risk of malignancy because of selection bias. Prior studies reporting lower malignancy rates (6.6%-18%) in pediatric thyroid nodules included smaller sample sizes and younger patients (13.1-14.6 vs 16.5 years of age).…”
Section: Original Article 348supporting
confidence: 80%
“…[1][2][3][4][5][6] In AUS/FLUS, the risk of malignancy in resected nodules is 5 to 15%, but a variation from 6 to 48% is in record. [6][7][8][9] It has been reported that with repeated FNAB in AUS/ FLUS cases, about 56 to 68% will have a more definitive result and 15.6 to 48.6% will be interpreted as AUS/FLUS. 7 The recommended management is clinical correlation and a repeat FNAB in 3 to 6 months.…”
Section: Introductionmentioning
confidence: 99%
“…10 It has been recommended that if there is an indication for surgical intervention, it is not necessary to repeat the FNAB. 4 Although it has been suggested that the usage of AUS/FLUS should not exceed 7% of thyroid FNABs, 3,7,9,10 there is variation of this percentage from 3 to 29% across laboratories and from 2.5 to 28.6% among cytopathologists. 5 Ultrasound findings can facilitate reaching a diagnosis of nodules with AUS/FLUS, 11 although they may not differentiate benign from malignant nodules.…”
Section: Introductionmentioning
confidence: 99%